(untitled) (NAU Journal of Technology and Vocational Education, 2024)
In order to carry out this study, two research questions and two null hypotheses were formulated. The study adopted descriptive survey research design. The population comprised 80 teachers and 54 instructors in technical colleges in South-East Nigeria and were studied without sampling. A structured and validated questionnaire containing 17 items was used for data collection. Cronbach alpha formula was used to determine the internal consistency of the questionnaire which yielded an overall reliability co-efficient of 0.77. The researchers administered the instrument with the help of five research assistants to the respondents. Data collected were analysed using weighted mean and improvement need index for both required and performance categories of the instrument in order to answer the research questions. The t-test was used to test the null hypotheses at 0.05 level of significance. Findings of the study revealed that mechanical craft teachers and instructors in technical colleges in South-East Nigeria need practical skills improvement for teaching drilling and milling practices. There is no significant difference between the mean responses of mechanical craft teachers and instructors on practical skills improvement needs for teaching drilling and milling practices in technical colleges South East, Nigeria. The study concluded that mechanical craft teachers and instructors in technical colleges in South-East Nigeria need practical skills improvement in drilling and milling practices in order to adequately prepare students to start their engineering venture upon graduation.